Analisis Pengaruh Saluran Komuikasi dan Keadaan Penyuluh Terhadap Adopsi Inovasi Combine Harvester di Kabupaten Tabanan - Paramarta, Pande Made Ari Ananta (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to analyze the influence of communication channels and the condition of instructors on the implementation of combine harvester machine innovations in Tabanan Regency. The data analysis used is descriptive statistics and the Partial Least Square (PLS) approach with the help of the smartPLS 3.0 application. The population of this study was 187 people. Determination of samples using the Slovin formula. Based on this population, the sample obtained was 66 farmers. The results of this research are that the communication channel variables received and the condition of the instructors are stated to have a significant positive effect on the adoption of invasion so that a hypothesis arises. The suggestion from this research is that the government is expected to improve programs that increase the knowledge and communication skills of agricultural instructors in Tabanan Regency. Farmers are expected to increase awareness that the agricultural sector requires the use of modern technology.